Factor II Activity is Similarly Increased in Patients With Elevated Apolipoprotein CIII and in Carriers of the Factor II 20210A Allele. Issue 6 (15th November 2013) - Olivieri, Oliviero; Martinelli, Nicola; Baroni, Marcello; Branchini, Alessio; Girelli, Domenico; Friso, Simonetta; Pizzolo, Francesca; Bernardi, Francesco
Abstract : Background: Few studies have so far investigated the relationship between apolipoprotein CIII (Apo CIII) and coagulation pathway in subjects with or without coronary artery disease (CAD). Methods and Results: Serum Apo CIII concentrations and plasma coagulant activities of factor II (FII:c), factor V (FV:c), and factor VIII (FVIII:c), and activated factor VII (FVIIa) were analyzed in a total of 933 subjects, with (n=687) or without (n=246) angiographically demonstrated CAD and not taking anticoagulant drugs. Activated factor X (FXa) generation assay was performed on plasma from subgroups of subjects with low and high levels of Apo CIII. A statistical incremental concentration of FII:c, FV:c, and FVIIa levels was observed through the quartiles of Apo CIII distribution in the population considered as a whole. Significant results were confirmed for FII:c in CAD and CAD‐free subgroup when separately considered. Subjects within the highest Apo CIII quartile (>12.6 mg/dL) had high FII:c levels not statistically different from those of carriers of 20210A allele (n=40; 4.28%). In a multiple linear model, Apo CIII was the best predictor of FII:c variability, after adjustment for age, gender, plasma lipids, CRP, creatinine, diagnosis, and carriership of 20210A allele. FXa generation was increased and its lag time shortened in plasmas with high Apo CIII levels. However, after thrombin inhibition by hirudin, differences between low and high Apo C‐III samples disappeared. Conclusions: Elevated concentrations of Apo CIII are associated with an increase of thrombin activity to an extent comparable with the carriership of G20210A gene variant and mainly modulating the thrombin generation.